Exploring the phylogeny of the marattialean ferns - Samuli Lehtonen; Péter Poczai; Gaurav Sablok; Jaakko Hyvönen; Dirk N. Karger; Jorge Flores (WILEY, 2022)
The eusporangiate marattialean ferns represent an ancient radiation with a rich fossil record but limited modern diversity in the tropics. The long evolutionary history without close extant relatives has confounded studies of the phylogenetic origin, rooting and timing of marattialean ferns. Here we present new complete plastid genomes of six marattialean species and compiled a plastid genome dataset representing all of the currently accepted marattialean genera. We further supplemented this dataset by compiling a large dataset of mitochondrial genes and a phenotypic data matrix covering both extant and extinct representatives of the lineage. Our phylogenomic and total-evidence analyses corroborated the postulated position of marattialean ferns as the sister to leptosporangiate ferns, and the position of Danaea as the sister to the remaining extant marattialean genera. However, our results provide new evidence that Christensenia is sister to Marattia and that M. cicutifolia actually belongs to Eupodium. The apparently highly reduced rate of molecular evolution in marattialean ferns provides a challenge for dating the key phylogenetic events with molecular clock approaches. We instead applied a parsimony-based total-evidence dating approach, which suggested a Triassic age for the extant crown group. The modern distribution can best be explained as mainly resulting from vicariance following the breakup of Pangaea and Gondwana. We resolved the fossil genera Marattiopsis, Danaeopsis and Qasimia as members of the monophyletic family Marattiaceae, and the Carboniferous genera Sydneia and Radstockia as the monophyletic sister of all other marattialean ferns.